Addition of Herbal Supplements in Feed on the Growth and Survival Rate of Cachama (Colossoma macropomum) with the Recirculation System - Pradana, Wishal Novan; Mulyadi, Mulyadi; Putra, Iskandar (Faculty of Fisheries and Marine, Universitas Riau, 2022)
This study aims to determine the best dose of herbal supplements in feed for growth and survival of Colossoma macropomum with a recirculation system. This research was conducted from 27 November - 6 January 2021 at the UPT Experiment Pool Faculty of Fisheries and Marine, University of Riau. The container used was a black tub with a volume of 100 L as many as 15 units with a stocking density of 20 individuals / 60 L. This study used a one-factor completely randomized design (CRD) method with five levels of treatment and three replications. The level of treatment applied in this study was P0 = without giving herbal supplements (control), P1 = doses of herbal supplements 100 mL / kg of feed, P2 = 200 mL/kg of feed, P3 = 300 mL / kg of feed, and P4 = 400 mL / kg of feed. The results showed that giving herbal supplements to feed with different doses had a significant effect (P <0.05) on growth but had no significant effect (P> 0.05) on the survival of Colossoma macropomum. The best treatment was found at the herbal supplement dosage of 300 ml / kg of feed, which resulted in absolute weight growth (24.24 g), absolute length growth (5.04 cm), specific growth rate (5.29%), feed efficiency (137, 96%), feed conversion ratio (0.72), survival rate (93.3%), total erythrocytes 1.64x104 cells / mm3, hemoglobin level 9.00 g/dL and blood glucose 89.33 mg/dL.